Improving the reading comprehension ability through webbing strategy - Suud Purnomo (Journal on English as a Foreign Language, 2012)
This study was designed to improve the students’ reading comprehension ability through webbing strategy which is designed to find a strategy of teaching reading skills in expository texts. The study employed a collaborative classroom action research design in which the researcher and the collaborator worked together designing the lesson plan, implementing the action, observing the action, and reflecting the action. The subjects of this research were 40 students the eleventh grade students of SMA PGRI Mojosari in the 2010/2011 academic year. The webbing strategy was successful in improving both the students’ ability in comprehending expository texts and the students’ involvement in reading activities. The strategy increased students’ mean scores and the students’ individual score percentage from preliminary study to Cycle 2 ranging from 64.83 to 78.17 or the students’ individual score percentage extended from 42.50% to 85% equal or greater than 70% of 40 students. The results of the second cycle indicated higher scores in which predetermined criteria of success met in the second cycle. The majority students showed active involvement (92.50%) in the third meeting of Cycle 2.